LAYANAN PEMINATAN DAN PERENCANAAN DALAM KURIKULUM MERDEKA BELAJAR DI SMA NEGERI 12 JAKARTA - Maulina, Dwi; Hajar, Siti (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Problems with specialization and planning services in schools are often caused by pressure from the social environment, a mismatch between students' interests and skills, and limited resources. SMA Negeri 12 Jakarta runs an merdeka belajar curriculum facing problems in implementing specialization and planning services, namely limited counseling teachers as resources. The purpose of the research is to describe the specialization and planning services implemented by counseling teachers at SMA Negeri 12 Jakarta and the problems faced in the merdeka belajar curriculum. The research method is descriptive qualitative. Through interview, observation, and documentation methods. The research subjects were the principal, vice principal for academic affairs, counseling teacher coordinator, and students. Data processing using the NVivo14 application results in the world cloud and project map. The results show that collaboration between counseling teachers, vice principals of academic affairs, subject teachers and parents can support the implementation of specialization and planning service programs in schools to help overcome the problems that occur in these schools.